Some Weighted Inequalities for Higher-Order Partial Derivatives in Two Dimensions and Its Applications - Samet Erden; M. Zeki Sarikaya (IndoMS, 2020)
We establish some Ostrowski type inequalities involving higher-order partial derivatives for two-dimensional integrals on Lebesgue spaces (L_∞, L_p and L₁). Some applications in Numerical Analysis in connection with cubature formula are given. Finally, with the help of obtained inequality, we establish applications for the kth moment of random variables.